Mitigating Multiple attacks in Cognitive Radio Networks - Jothiraj, Sivasankari; Balu, Sridevi (International Journal of Engineering and Technology, 2018)
Database driven CRNs are taken into consideration because the promising technique to enhance the wireless spectrum usage, it faces serious safety demanding situations via location cheating attack. The number one challenges are location proof verification and region solitude verification. Malicious users create a faux region with the aid of self-seeking the all to be had spectrum bands. A region based totally service is used for imparting provider to the consumer. Wi-Fi authority verifies the place whether or not the proof is legitimate or no longer. If the person is valid, it passes the facts to the base station. This technique provides effective reduction of malicious user in the cognitive radio community.Â Â